Pengaruh Promosi terhadap Keputusan Pembelian Pakaian pada Toko Qolsa Metro Tahun 2022 - Ningrum; Lilian Mega Puri; Eva Ratnasari (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
Promotion is a communication activity carried out by a person or company with the broader community, where the aim is to introduce something (goods/services/brands/companies) to the community and at the same time influence the wider community to buy and use the product. Purchasing decisions are a process where consumers choose and evaluate products or services, often consumers consider various things that suit their needs in the purchase decision process. Every company built by a business entity or individual is generally the same, namely, to seek as much profit as possible by increasing purchases at the company, it takes various kinds of marketing activities, one of which is to hold promotional activities for the products produced, with the existence of marketing activities. Sales promotion in each company will indirectly help increase purchases of products. This study aims to determine how much influence promotion has on purchasing decisions at the Qolsa Fashion Store. The type of research used is quantitative research. The population in this study were all consumers of the Qolsa store in the metro city. In this study, samples were taken from many as 50 respondents. Data was taken through a questionnaire method. Data processing is done with the help of Microsoft Excel. The test includes a validity test, reliability test, normality test, homogeneity test, simple linear regression test, F-test, and t-test. The results show that there is a significant positive effect of promotion on purchasing decisions. The results of this study indicate that: There is a promotion effect on purchasing decisions for clothing at the Qolsa store in 2022 with the regression equation Y = 44.324 + 0.3233 X can be seen from the results of the analysis of the calculation of the value of t-count and t-tab above, it means that it is known that t-count > t-tab can be seen in the table of t point on the 5% significant list, namely 2.65> 1.68 also the Fcount value of 4.28 is greater than Ftab = 4.04 which is 4.28> 4.04 means There is a Significant Effect of Promotion on Purchase Decisions Clothing at Qolsa Stores in Metro City in 2022.